2022
DOI: 10.1177/2057150x221114599
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in China: A review and new findings

Abstract: In the past four decades, sexuality research in China has made considerable advancements. From historical and sociological perspectives, our study reviews the literature and provides a comprehensive overview of sexuality in contemporary China by drawing on recent survey data that we collected. First, we introduce sexuality in ancient and modern China and discuss the social contexts that gave rise to a sexual revolution in China. Second, we briefly review empirical research on sexuality in China. Finally, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…Compared to the twentieth century, the living conditions of sexual minority populations in China do not seem to have changed much and lesbians have always been more hidden and invisible than gays [63]. According to a recent national survey on sexuality in China, for women born in the 1980s and 1990s (similar to the age group of the population surveyed in this study), 30.3% and 18.1%, respectively, believe homosexual sex is always wrong, and both rates are higher among men in the same age groups [64].…”
Section: Principal Findingsmentioning
confidence: 59%
“…Compared to the twentieth century, the living conditions of sexual minority populations in China do not seem to have changed much and lesbians have always been more hidden and invisible than gays [63]. According to a recent national survey on sexuality in China, for women born in the 1980s and 1990s (similar to the age group of the population surveyed in this study), 30.3% and 18.1%, respectively, believe homosexual sex is always wrong, and both rates are higher among men in the same age groups [64].…”
Section: Principal Findingsmentioning
confidence: 59%
“…Homosexual people may be more prone to use pornography owing to sexual‐orientation‐related information‐seeking and/or scarcity of potential romantic or sexual partners (Bőthe et al, 2020). Another possible reason is that sexual‐minority men are less likely than their heterosexual peers to receive sexual education and information that addresses male–male sexual relationships from traditional sources (e.g., school, parents/guardians; Nelson, Pantalone, et al, 2019), especially in China (Yu et al, 2022). To learn more about sexual expression and intimacy and other related information, multiple sexual minorities have turned to internet sources, including online media (Nelson, Carey, et al, 2019), and consumption of online pornography may help affirm homosexual identity (Giano, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Grubb & Turner, 2012; Li & Zheng, 2022; Xue & Lin, 2022). Second, we include age in our analysis as previous studies point out that younger generations are associated with more liberal sexual attitudes (Yu et al, 2022), which could link to a lower level of endorsement of rape myths. Participants’ age is measured in years as a continuous variable.…”
Section: Methodsmentioning
confidence: 99%
“…Rape survivors were even socially required to restore their own and families’ reputations by committing suicide after being raped, as death was viewed as a smaller matter compared to a loss of sexual virtue (Ng, 1987). Despite the fact that younger generations demonstrate more liberal sexual attitudes compared to the past (Yu et al, 2022), the high value attached to female virginity and chastity is still present today (Lyu et al, 2020). Luo (2000), from her interviews with 35 rape survivors in Taiwan, which shares a broader Chinese cultural practice, found that these survivors felt a strong sense of guilt in imposing social disgrace on their family members.…”
Section: Age and Rape Perception In Chinamentioning
confidence: 99%